The Role of Motivation Mediation on the Effect of Transformational Leadership Style on Employee Performance - Muhamad Ekhsan; Indra Setiawan (Lembaga Komunitas Informasi Teknologi Aceh (KITA), Indonesia, 2021)
This research was conducted to determine the effect of transformational leadership style on employee performance mediated by work motivation variables. This type of research is explanatory research with a quantitative approach. In this study, the data used are primary data obtained and collected through direct surveys using questionnaires to respondents. Sampling in this study using a random sampling method with samples taken as many as 67 employees. PT. Maxalmina Compressed Natural Gas Transportation. Explanatory methods and Structural Equation Modeling (SEM) are used to explain between variables. In analyzing the data in this study, evaluation of Outer model, evaluation of the Inner model, evaluation of Goodness of fit, and testing of the research hypothesis using Bootstrapping was carried out. The results of this study indicate that transformational leadership style has a positive and significant effect on employee performance, transformational leadership style has a positive and significant effect on motivation, work motivation has a positive and significant effect on employee performance. This study also proves that work motivation is successful in mediating the effect of transformational leadership style on employee performance.